Risk Factors of Gestational Diabetes Mellitus in a Reference Maternal Health Care Centre in Southern Benin - OGOUDJOBI, OGOURINDÉ MATHIEU; LOKOSSOU, Mègnissè Sèna H. S.; TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE; DENAKPO, Justin Lewis; PERRIN, RENÉ-XAVIER (My University, 2017)
Gestational diabetes mellitus is the most commonly observed endocrine disorder during pregnancy. It results in severe fetal and maternal complications that can increase the fetal morbidity and mortality and the risk for overt diabetes in women. Identification of pregnant women at high risk for gestational diabetes mellitus is therefore needed for early detection in order to reduce its consequences for the mother, the fetus and the newborn. The objective of the study was to identify risk factors for gestational diabetes in a reference maternal health care centre in southern Benin. This was a case-control study carried out from 1st February 2015 to 31st July 2017 in reference maternal health care centre at the University Hospital of Porto-Novo. All pregnant women with a gestational age of 24 to 28 weeks of amenorrhea, who utilized antenatal care service of University Hospital of Porto-Novo, were screened for gestational diabetes mellitus. The chi-square test was used to identify risk factors for gestational diabetes mellitus. The statistical significance was fixed at p < 0.05. Of the 967 pregnant women participated in the study, 73 cases of gestational diabetes mellitus, were detected (7.5%). Risk factors of gestational diabetes identified were: maternal age ≥ 35 years [OR 7.82 CI 95% (4.75-12.89)], body mass index ≥ 25 kg/m2 [OR 9.56 CI 95% (5.17-17.70)], family history of diabetes at 1st degree [OR 2.78 CI 95% (1.53-5.06)], a history of fetal macrosomia [OR 7.25 CI 95% (3.11-16.92)], a history of stillbirth [OR 2.98 CI 95% (1.78-5.00)], an antecedent of more than two spontaneous miscarriages [OR 1.93 CI 95% (1.19-3.12)] and the personal history of hypertension [OR 3.91 CI 95% (1.52-10.07)]. This study confirmed the influence of maternal age and some medical and obstetric histories as risk factors of gestational diabetes mellitus. These pregnant women at high risk of gestational diabetes mellitus should benefit from early detection.
Keywords: Gestational Diabetes Mellitus; Risk Factors; WHO Test